2014
DOI: 10.1186/1471-2407-14-994
|View full text |Cite
|
Sign up to set email alerts
|

The association between Histone 3 Lysine 27 Trimethylation (H3K27me3) and prostate cancer: relationship with clinicopathological parameters

Abstract: BackgroundIt is well established that genetic and epigenetic alterations are common events in prostate cancer, which may lead to aberrant expression of critical genes. The importance of epigenetic mechanisms in prostate cancer carcinogenesis is increasingly evident. In this study, the focus will be on histone modifications and the primary objectives are to map H3K27me3 marks and quantify RAR beta 2, ER alpha, SRC3, RGMA, PGR, and EZH2 gene expressions in prostate cancer tissues compared to normal tissues. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 41 publications
1
32
1
Order By: Relevance
“…2 That study provided a clue on the role of SKP2 on histone modifications and the epigenetic alterations in PCa. Although levels of SKP2 and Enhancer of zeste homolog 2 (EZH2) are highly associated with aggressive features of human PCa, 1,14 it remains unclear whether SKP2 determines the levels of histone H3 lysine 27 trimethylation (H3K27me3) state by modulating EZH2.…”
Section: Introductionmentioning
confidence: 99%
“…2 That study provided a clue on the role of SKP2 on histone modifications and the epigenetic alterations in PCa. Although levels of SKP2 and Enhancer of zeste homolog 2 (EZH2) are highly associated with aggressive features of human PCa, 1,14 it remains unclear whether SKP2 determines the levels of histone H3 lysine 27 trimethylation (H3K27me3) state by modulating EZH2.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancer of zeste 2 polycomb repressive complex 2 subunit, a methyl-transferase for H3K27, is upregulated in a variety of tumors and serves an essential role in tumor promotion (2,16); our previous study reached the same conclusion (17). Certain studies have widely associated H3K27me3 with gene silencing and transcriptional inhibition (6,18); however, these studies have not achieved a consensus on the level of H3K27me3 and the significance of its aberrant expression in human tumorigenesis. Previous studies have suggested that the low expression level of H3K27me3 in tumor tissues may enhance the expression of oncogenes and consequently promote tumor growth (19)(20)(21)(22); however, Nakazawa et al (23) revealed no significant differences when comparing the expression levels of H3K4me2 and H3K27me3 in 85 cases of colorectal cancer with the paired normal colorectal tissues.…”
Section: Discussionmentioning
confidence: 75%
“…1B). AR mRNAs were evaluated by reverse transcriptase (RT)-quantitative polymerase chain reaction (Q-PCR) (Ngollo et al, 2014) as shown in Figure 2A and were found highly expressed in the LAR subtype compared with the basal-like subtypes with a significant difference ( p = 0.029).Therefore, H3 modifications on AR promoter gene were studied in LAR and basal-like subtypes by immunoprecipitation of chromatin (Dagdemir et al, 2013;Ngollo et al, 2014) following by Q-PCR (Fig. 2B).…”
mentioning
confidence: 99%
“…1B). AR mRNAs were evaluated by reverse transcriptase (RT)-quantitative polymerase chain reaction (Q-PCR) (Ngollo et al, 2014) as shown in Figure 2A and were found highly expressed in the LAR subtype compared with the basal-like subtypes with a significant difference ( p = 0.029).…”
mentioning
confidence: 99%
See 1 more Smart Citation